Exponentiated Generalized Weibull Exponential Distribution: Properties, Estimation and Applications - Anuwoje Ida L. Abonongo; John Abonongo (Computational Journal of Mathematical and Statistical Sciences)
Real-life sciences rely heavily on statistical modeling because new applications and phenomena pop up constantly, increasing the demand for new distributions.